The Role of Leadership In Increasing Employee Morale at The Regional Inspectorate of West Kutai Regency - Dewi Viayanti Mala; Agustinus Djiu; Musmuliadi Musmuliadi (Journal Research of Social Science, Economics, and Management, 2022)
Human resources are a very important factor in an organization, both large and small organizations. In large-scale organizations, human resources are seen as a very decisive element in the business development process, the role of human resources is becoming increasingly important. This study aims to determine the personal role of the leader in increasing the morale of the employees of the Regional Inspectorate of West Kutai Regency, to determine the role of leader decision-making in increasing the morale of the employees of the Regional Inspectorate of West Kutai Regency and to determine the role of the leader in utilizing information sources in increasing the morale of the Regional Inspectorate's employees West Kutai Regency. This research is a type of research that uses a qualitative approach as a research procedure that produces a description in the form of written and spoken words of people and observable behavior, which is carried out at the Regional Inspectorate Office of West Kutai Regency. The research period is from 2020 to 2021. The Inspectorate of the Regional Inspectorate of West Kutai Regency has directly or indirectly provided decision making to its members so that their employees can find out from what has been given by the Regional Inspectorate of Kutai Barat Regency in order to increase employee morale at the Regional Inspectorate Office of West Kutai Regency, which is carried out The Inspectorate of the Regional Inspectorate of West Kutai Regency in making policies for his employees, namely the Regional Inspectorate of the West Kutai Regency Inspectorate always leaves the initial office of his employees and returns to the last office of his employees